2022
DOI: 10.1149/1945-7111/ac811d
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Effect of Low Pt Loading Cathode Catalyst Layer in Polymer Electrolyte Fuel Cells. Part II: Parametric Analysis

Abstract: A parametric analysis is presented using a previously validated 1D model for a cathode catalyst layer (CL). The results show that maximum power density at low Pt loading can be maximized with relatively thin CLs (${\rm thickness}\sim 2\;\mu \rm m$) featuring a high carbon volume fraction (low ionomer-to-carbon weight ratio, I/C) compared to high Pt loading CLs. The shift of the optimal carbon volume fraction (I/C ratio) is caused by the dominant role of the local oxygen transport resistance at low Pt loading, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 59 publications
2
8
0
Order By: Relevance
“…Similarly, several studies have reported that an ultra-thin water layer on the surface of Pt generates local O 2 transport resistance under high current density, which contributes to R total significantly. 30,50,51 Thus, it is evidenced that CCL confronts several challenges, which significantly influence the cell performance. These challenges encompass multifaceted issues such as the heightened resistance encountered in the local O 2 transport, limited mass transfer at the ionomer/Pt interface, and CCL flooding due to the accumulation of H 2 O by-products.…”
Section: Table 1 Properties and Performance Of Pt-based Cclsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, several studies have reported that an ultra-thin water layer on the surface of Pt generates local O 2 transport resistance under high current density, which contributes to R total significantly. 30,50,51 Thus, it is evidenced that CCL confronts several challenges, which significantly influence the cell performance. These challenges encompass multifaceted issues such as the heightened resistance encountered in the local O 2 transport, limited mass transfer at the ionomer/Pt interface, and CCL flooding due to the accumulation of H 2 O by-products.…”
Section: Table 1 Properties and Performance Of Pt-based Cclsmentioning
confidence: 99%
“…Similarly, several studies have reported that an ultra-thin water layer on the surface of Pt generates local O 2 transport resistance under high current density, which contributes to R total significantly. 30,50,51…”
Section: Introductionmentioning
confidence: 99%
“…The local oxygen resistance per unit of active catalyst surface area, R i O2 , and the local oxygen resistance per unit of geometric area, R local O2 , are related by the roughness factor (Sánchez-Ramos et al, 2021;Sánchez-Ramos et al, 2022)…”
Section: Effect Of Relative Humidity Temperature and Pressurementioning
confidence: 99%
“…), while ∆φ p was directly taken as the prescribed potential drop (∆φ p = 1). According to Equations (4a) and (4b), the local resistance per unit of the geometric area is inversely proportional to the roughness factor (R local ∝ r −1 f ), dramatically increasing at low Pt loading when A Pt → 0 [13,14,44]. Pt was assumed to be well dispersed over Pt surface, so no explicit description of the Pt nano-particle shape was made (A c A Pt ).…”
Section: Numerical Modelmentioning
confidence: 99%